Perkawinan Berbeda Agama Di Indonesia - I Gede Krisna Andyka Pramana Putra; Luh Merry Dyanthi; Deli Bunga Saravistha; Kadek Mery Herawati (Indra Institute Research & Publication, 2023)
In general, interfaith marriages can result in distinct legal issues for both the husband and wife and for outsiders or third parties, such as concerns regarding the inheritance rights of children born to interfaith couples. the legality of marriage, which will give husband and wife rights and responsibilities. The wife's entitlement to maintenance and joint assets is entirely contingent on the existence of a legally binding marriage and the likelihood that she will bear legal children. Naturally, a marriage has legal repercussions, and if it is interfaith, there will undoubtedly be a variety of issues. These issues affect the relationship between the husband and wife and, if they have children, their children. Both psychological and judicial consequences from a legal standpoint. Marriages between people of different religions are a fact of life that cannot be denied. In reality, many couples want to live together, but they cannot get married because their religions or beliefs are different.